Pengembangan Bahan Ajar Modul dengan Pendekatan Discovery Learning pada Materi Himpunan - Nanik Saputri; Isnaini Nur Azizah; Hernisawati Hernisawati (Department of Mathematics, Universitas Negeri Gorontalo, 2020)
This research generally aims to produce Module teaching material products with the Discovery Learning approach to the set material, and the specific purpose is to find out how the development and attractiveness of the Module teaching materials with that approach. This study uses the Thiagarajan 4D model development method, which consists of 4 stages, namely definition, design, development, and dissemination. The results of the research on the development of the Modules teaching material with the Discovery Learning approach. : (1) The main results of this research and development are Module teaching materials with the Discovery Learning approach. (2) Research data shows that material experts obtained an average value of 76% with the criteria of